2014
DOI: 10.1038/bjc.2014.492
|View full text |Cite
|
Sign up to set email alerts
|

PKM2 as a biomarker for chemosensitivity to front-line platinum-based chemotherapy in patients with metastatic non-small-cell lung cancer

Abstract: Background:Tumour cells exclusively express the embryonic M2 isoform of pyruvate kinase (PKM2). PKM2 expression levels have been correlated with the effect of platinum compounds in cancer cell lines and xenograft models. The potential predictive role of PKM2 in patients with metastatic/advanced non-small-cell lung cancer (NSCLC) receiving platinum-based chemotherapy as first-line was investigated.Methods:Quantitative real-time PCR was used to assess the expression of PKM2 in tumour samples from 148 and 157 NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…PKM2, as the critical isoenzyme of PK, serves a role in maintaining the metabolic program of cancer cells (34). inhibition of PKM2 expression was previously reported to decrease glucose consumption and lactate production (35), and elevated expression of PKM2 has been reported in colon and lung cancer (36,37). Previous studies have suggested that PKM2 contributes to cancer metabolism by promoting hypoxia-inducible factor-1 expression or coordinating with c-Myc (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…PKM2, as the critical isoenzyme of PK, serves a role in maintaining the metabolic program of cancer cells (34). inhibition of PKM2 expression was previously reported to decrease glucose consumption and lactate production (35), and elevated expression of PKM2 has been reported in colon and lung cancer (36,37). Previous studies have suggested that PKM2 contributes to cancer metabolism by promoting hypoxia-inducible factor-1 expression or coordinating with c-Myc (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…These findings also highlight a role of PKM2 in facilitating cancer cells to survive chemotherapy, the application of DNA damage in treating diseases, making it a new target in preventing cancer development and chemotherapy resistance (38).…”
Section: Discussionmentioning
confidence: 82%
“…identification of eight prognostic biomarkers for feature selection. We referred to seven well-known biomarkers that are highly correlated with NSCLC according to previous studies (EPCAM, HIF1A, PKM, PTK7, ALCAM, CADM1, and SLC2A1) [5][6][7][8][9][10][11]24,25 . Based on each of these seven biomarkers, we separated the 614 ADC patients into biomarker-and biomarker+ subgroups according to expressions by StepMiner 26 (Fig.…”
Section: Figurementioning
confidence: 99%